PENGARUH MOTIVASI KERJA TERHADAP TARGET PENJUALAN DI PT SINAR GRIYA UTAMA - ., Syahyono (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2015)
The purpose of this study is to determine the effect of employee motivation on the level of sales in PT.Sinar Griya Utama. The foregoing can not be achieved if there is no good cooperation between employees and the company. A good motivation between supervisors and subordinates to achieve the targets of the company. Motivation as a human impulse. However, is very important for the target of the marketing to be equal with the duties and the functions of employees. Impulses that exist on employees, neither arise from inside himself or outside himself, greatly affect motivation.Good level of sales would be achieved when the employees intentionally join motivational seminars, which may raise employees’ spirit, so that the level of sales could be achieved. This study aims to identify and obtain a description, as well as examine the role of the employee motivation on the level of sales at PT. Sinar Griya Utama.